Analisis Segitiga Cinta Pada Tokoh Timur Dalam Cerpen Harapan Karya Fiersa Besari: Kajian Psikologi Sternberg - Nadila Faridatunisa; Arda Rahmawati; Eva Dwi Kurniawan (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research began with the love relationship in the short story Harapan in the book 11:11 by Fiersa Besari. This love relationship originates from the figures of Timur and the sun. Starting from a love relationship, the problem arises of finding answers to questions regarding the components of love in that relationship. The aim of this research is to determine the form of love for 'Eastern' characters in literary works. The work taken is in the short story genre entitled Hope by Fiersa Besari. The problem in this research is how their relationship is in establishing interpersonal relationships in the short story. The method used is a descriptive qualitative research method, while the data used is note-taking using Sternberg's psychological approach regarding the Tringular theory of love. The research results obtained show that Timur and Mentari stores have components of intimacy and commitment. The research results show that the love relationship between Timur and Mentari is affective love.